How to fossilise your hamster : and other amazing experiments for the armchair scientist - O'Hare, Mick (Profile, 2007)
How can you measure the speed of light with a bar of chocolate and a microwave oven? To keep a banana from decaying, are you better off rubbing it with lemon juice or refrigerating it? How can you figure out how much your head weighs? Mick O'Hare, who created the New Scientist's popular science sensations Does Anything Eat Wasps? and Why Don't Penguins' Feet Freeze?, has the answers. In this fascinating and irresistible new book, O'Hare and the New Scientist team guide you through one hundred intriguing experiments that show essential scientific principles (and human curiosity) in action. Explaining everything from the unusual chemical reaction between Mentos and cola that provokes a geyser to the geological conditions necessary to preserve a family pet for eternity, How to Fossilize Your Hamster is fun, hands-on science that everyone will want to try at home.